Development of E-LKPD Based on Kvisoft Flipbook Maker to Improve Concept Understanding of Class X Students on Global Warming Materials Manuscript - Yulianuzha Yulia; Heru Kuswanto (Postgraduate, University of Mataram, 2023)
This research is a development research with the aim of developing learning media based on kvisoft flipbook maker on Global Warming material in order to improve understanding of concepts in class X high school students. This type of research is the development of Research and Development (R&D). The design of this study uses the ADDIE (Analysis, Design, Development, Implement, and Evaluation) model. The research subjects consisted of 26 students in each control and experimental class. The sample in this study was determined by random sampling. The instrument used is an assessment scale to determine the quality of the developed learning media and a concept understanding test to determine students' conceptual understanding. The software used to develop this learning media is kvisoft flipbook maker. Validation was carried out by 3 expert validators and students. Analysis of the data used is SBi to analyze the feasibility of the media and the Mann Whitney Test. The results showed that the kvisoft flipbook maker-based E-LKPD was feasible to be used in improving understanding of the concept of Global Warming in class X high school students. This was based on the average number of learning media feasibility scores by expert validators was 4.6 which means â‰¥4.21 and the average score of the students' assessment is 3.6, which means â‰¥3.0. The post-test average score of students' conceptual understanding in the control class was 70.58, while in the experimental class it was 83.85. Then from the results of the non-parametric test, the output of the test statistics is known as Asym.Sig (2-talled) with a value of 0.049 which means Î±Ë‚0.05.